2022
DOI: 10.3390/jcm11154566
|View full text |Cite
|
Sign up to set email alerts
|

Current Status of Internet Gaming Disorder (IGD) in Japan: New Lifestyle-Related Disease in Children and Adolescents

Abstract: The World Health Organization recognizes Internet gaming disorder (IGD) as a disorder that causes problems in daily life as a result of excessive interest in online games. The causes of IGD have become more apparent in recent years. Because of prolonged exposure to games, the mechanisms controlling the reward system, such as the prefrontal cortex, limbic system, and amygdala of the cerebrum, do not function properly in IGD. This mechanism is similar to that of various behavioral addictions, such as gambling ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 76 publications
1
11
0
2
Order By: Relevance
“…Further, the core pathol-ogy of GD includes psychological dependence. Additionally, individuals with GD exhibited personal features similar to traditional substance-related addicts, including the reduced personal capacity to evaluate risks, aggression, and impulsivity [89]. In line with this, another study underlined the addictive potential of problematic online gaming compared to other online activities.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Further, the core pathol-ogy of GD includes psychological dependence. Additionally, individuals with GD exhibited personal features similar to traditional substance-related addicts, including the reduced personal capacity to evaluate risks, aggression, and impulsivity [89]. In line with this, another study underlined the addictive potential of problematic online gaming compared to other online activities.…”
Section: Discussionmentioning
confidence: 77%
“…Other factors that might contribute to these findings are recent changes in the young population's lifestyle. Notably, multiple observations were reported on excessive gamer lifestyles, including increased nighttime activity, altered sleep-wake cycles, and altered eating habits [89].…”
Section: Discussionmentioning
confidence: 99%
“…Una parte de estas investigaciones se ha concentrado en una perspectiva vinculada al carácter benigno de los videojuegos, identificando los probables beneficios de su uso en las áreas cognitiva (Brilliant et al, 2019;Huan & Cheng, 2022;Reynaldo et al, 2021), emocional (Cabelkova et al, 2020), motivacional (Granic et al, 2014) y social (Granic et al, 2014;Lobel et al, 2017;Wiederhold, 2021). No obstante, más allá de esta representación positiva, la comunidad científica ha dispuesto su atención en el potencial adictivo de los videojuegos y en sus efectos sobre la salud mental de los usuarios (Chung et al, 2018;Giustiniani et al, 2022;Kim et al, 2008;King & Delfabbro, 2014;Imataka et al, 2022;Turel et al, 2016).…”
Section: Eunclassified
“…9,[15][16][17] Internet gaming disorder affected the participants' sleep patterns, many studies reported on it. 16,[18][19][20][21][22] The presence of IGD was significantly linked to those who used smartphones. 23 Gaming frequently functions as a passive coping mechanism in response to unpleasant emotions and/or real-life challenges.…”
Section: Introductionmentioning
confidence: 99%